Teledermatology and teledermatopathology as educational tools for international dermatology: a virtual grand rounds pilot curriculum. (24th April 2018) - Yeung, Howa; Sargen, Michael R.; Luk, Kevin M.; Berry, Elizabeth G.; Gurnee, Emily A.; Heuring, Erin; McMichael, Josette; Chen, Suephy C.; Stoff, Benjamin K.
Abstract: Background: Teledermatology may improve dermatologic care access in underserved areas and expand the clinical experience of dermatologists‐in‐training. The potential for teledermatology to supplement global health curricula in dermatology residency education has not been explored. Methods: An international virtual grand rounds (VGR) curriculum was created based on teledermatology cases from Kabul, Afghanistan. The learning objectives included understanding the diagnosis and management of skin diseases in unfamiliar resource‐limited settings and highlighting socioeconomic, cross‐cultural, and ethical issues. A 17‐item, Likert scale questionnaire was used to assess the effectiveness of the curriculum, including specific Accreditation Council for Graduate Medical Education (ACGME) competencies, as well as interest in global health and teledermatology. Results: The survey was completed by 85 of 118 VGR attendees (72% response rate). Most respondents considered the curriculum valuable to their education (mean 4.5 on a 5‐point Likert scale; standard deviation, 0.5), learned more about diagnosis and treatment of skin diseases in international settings (4.5; 0.6) and in the US (4.1; 0.8), and learned more about socioeconomic, cultural, and ethical issues in skin health (4.6; 0.5). The majority also reported being more interested in global dermatology (4.1; 0.8) and would recommend VGR to a colleague (4.5; 0.6). Conclusion: This pilot curriculum provided an innovative platform to enhance undergraduate and graduate medical education in international dermatology. International teledermatology education may be used to address multiple ACGME core competencies and increase resident awareness of sociocultural determinants of skin health.